Gains from multinational competition for crossborder firm acquisition - Onur A. Koska (Kiel Institute for the World Economy (IfW), 2018)
This study shows that when there is multinational competition for foreign acquisition, the strategic use of a consumer welfare argument in regulating foreign market entry leads to a preemptive foreign acquisition. Even under fierce competition, foreign acquisition will emerge as part of a non-cooperative equilibrium (although multinationals would have gained more had they been able to credibly commit to a cooperative equilibrium of independent foreign sales, either via greenfield investment or trade under complete liberalization) which increases local welfare by more than both the case without foreign market entry and the case with foreign market entry via independent foreign sales.
Keywords: F23; 330; cross-border firm acquisitions; foreign market entry regulations; greenfield investment; trade; consumer welfare